PowerShell for sysadmins : workflow automation made easy - Bertram, Adam Richard (No Starch Press, 2020)
"A practical guide to using PowerShell. Begins with an introduction for new users, then moves on to explaining how to develop scripts to automate daily tasks, and finally teaches how to build a large project to automate server deployments from scratch."--